Polydopamine Core Half-Polyamidoamine Dendrimers Based Drug-Delivery Platform and Characterization by Electrochemical Impedance Spectroscopy. Issue 10 (18th July 2015) - Ge, Hanli; Kong, Yong; Pan, Yan; Deng, Linhong; Shou, Dan; Lu, Qingyun
Abstract : Dopamine was self-polymerized onto the surface of a glassy carbon electrode (GCE), and the obtained polydopamine (PDOA) functioned as a scaffold for the grafting of half-polyamidoamine (H-PAMAM) dendrimers, which is a new class of polymeric biomaterial as drug carriers. Aspirin was chosen as the model drug and loaded into the H-PAMAM dendrimers via ion pairing, hydrogen bonding and hydrophobic interaction. The synthesis of H-PAMAM dendrimers grafted PDOA was characterized by electrochemical impedance spectroscopy (EIS), attenuated total reflection infrared spectroscopy (ATR-IR), atomic force microscopy (AFM), transmission electron microscopy (TEM), UV-visible spectroscopy and water contact measurement. The process of aspirin loading and delivery was also monitored by EIS. The results demonstrate that PDOA films can be used as an excellent platform for grafting of H-PAMAM dendrimers, which is an ideal carrier for drug loading and delivery.